Classical solutions in quantum field theory : solitons and instantons in high energy physics - Weinberg, Erick J. (Cambridge monographs on mathematical physics., 2012)
"Classical solutions play an important role in quantum field theory, high-energy physics, and cosmology. Real-time soliton solutions give rise to particles, such as magnetic monopoles, and extended structures, such as domain walls and cosmic strings, that have implications for the cosmology of the early universe. Imaginarytime Euclidean instantons are responsible for important nonperturbative effects, while Euclidean bounce solutions govern transitions between metastable states. Written for advanced graduate students and researchers in elementary particle physics, cosmology, and related fields, this book brings the reader up to the level of current research in the field"--